2018
DOI: 10.1080/10439463.2018.1467906
|View full text |Cite
|
Sign up to set email alerts
|

Variation in detainee risk assessment within police custody across England and Wales

Abstract: Every time a person is booked into police custody in England and Wales, they are assessed for risk of harm to themselves or others. National guidance is provided on what questions should be asked as part of this process; however, each year there are still instances of serious adverse incidents, self-harm and deaths in custody. The purpose of this study is to look at the extent to which the national guidance is being followed and the extent to which the risk assessment process varies between police forces. A Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…To enhance the methodology further, the statistical analysis could be applied to a larger dataset to explore the impact of demographic and socio-economic variables on risk as these did not feature in the current models but it is unclear as to whether this was influenced by missing data. As highlighted in the introduction, risk assessment content varies between forces (Stoneman et al 2018) so further research should consider using data from different forces to examine whether the same variables are significant, or whether there are other variables captured by other forces, but not in this dataset, that would be included due to their association with Observation Level. In addition, any risk assessment is only as useful as the information on which it is based, and it is acknowledged that detainees may not always reveal personal information about risks.…”
Section: Discussion and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the methodology further, the statistical analysis could be applied to a larger dataset to explore the impact of demographic and socio-economic variables on risk as these did not feature in the current models but it is unclear as to whether this was influenced by missing data. As highlighted in the introduction, risk assessment content varies between forces (Stoneman et al 2018) so further research should consider using data from different forces to examine whether the same variables are significant, or whether there are other variables captured by other forces, but not in this dataset, that would be included due to their association with Observation Level. In addition, any risk assessment is only as useful as the information on which it is based, and it is acknowledged that detainees may not always reveal personal information about risks.…”
Section: Discussion and Further Researchmentioning
confidence: 99%
“…Currently, there is little empirical evidence as to the effectiveness of the data collected during risk identification in being able to predict risk of harm, or which factors have the highest weighting. In fact, recent research has shown that what is actually included in the risk assessment varies from the questions in Table 2 and from force to force, with police forces adding their own questions to supplement the guidance (Stoneman et al, 2018) suggesting that forces do not feel the guidance is identifying risk appropriately. An example of this is around alcohol consumption, which is not included in the guidance as a question, yet the majority of forces ask questions around this (Stoneman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise findings from the ongoing review remain to be seen, early evidence suggests that Irish police risk assessment practices will be re-tailored for the purpose, not singularly of managing risk (through a focus on issues of mental health), but also to facilitate the appropriate identification of suspects with intellectual disabilities at the point of first contact with the Irish criminal justice system (An Garda Siochana, 2020). In proposing to elongate Ireland's existing risk assessment protocol so as to accommodate a vulnerability assessment (by including a new section relating specifically to intellectual disability), the review's findings promise to avoid the diagnostic shortcomings historically associated with the exclusive use of risk matrices to identify intellectual disability (Stoneman et al, 2019). Indeed, the urgent unmet need for mainstreaming such a vulnerability assessment within Irish police procedure is evident from the recent empirical inquiry that excavated concerns amongst criminal justice stakeholders with regard to the capacity of Irish police officials to identify intellectual disabilities (Gulati et al, 2021a).…”
Section: Review Of Risk Assessment Practicesmentioning
confidence: 99%
“…In addition, COs also record their own observations about these and other relevant issues. Recent research has shown that in practice, the questions asked and observations recorded as part of this process varies greatly not only from this guidance, but also between police forces (Stoneman et al 2018). The assessment of detainee risk then leads to a decision by the CO as to which support services need to be accessed, but also what observation level a detainee should be placed on.…”
Section: Police Custodymentioning
confidence: 99%